Do we still adhere to the norms of ancient Egypt? A comparison of Ptahhotep's communication ethics with current regulatory principles. (October 2019) - Löwstedt, Anthony
Values and norms for communication expressed in the ancient Egyptian treatise, The Teachings of Ptahhotep, are compared to current regulatory communication standards, especially the IFJ Declaration of Principles on the Conduct of Journalists, and to liberal and socialist ideologies. Ptahhotep argued in favour of basic equalities, respect, and the free flow of information and opinions, particularly for political speech, much like social democracy and political liberalism do. He also set limits regarding freedom of communication similarly: for hate speech, incitement to violence, defamation, invasion of privacy and concentration of ownership. The close parallels between the principles of communication ethics in ancient Egypt and today are partly explained with a look at similarly restructuring powers of innovative phonographic media (writing) then and prographic (electronic programming) media now, and partly with (indirect) influence. The article also asks whether the concept of 'Western civilization' should continue to exclude ancient Egypt.